Energy conversion from DC generator part in wind turbine to produce electricity - Nurul Hafizah, Abdullah Hasim (2013)
A wind turbine is a rotating machine which converts the kinetic energy of wind into mechanical energy. If the mechanical energy is used directly by machinery, such as a pump or grinding stones, the machine is usually called a windmill. If the mechanical energy is instead converted to electricity, the machine is called a wind generator, or more commonly called a wind turbine. This study presents of doing an experiment of a simple wind turbine. The project is to analyze the suitable DC motor that can act as generator part in wind turbine and operate properly. Besides that, the wind turbine should generate electricity as it functions. For this process, after choosing the suitable DC generator, an experiment was undergone to determine the output voltage which is the electricity and also to check whether the DC generator operates properly. Actually the experiment was undergone using wind velocity that can be gain around us but because the wind velocity is too slow and not windy, I am using the wind velocity from fan and act as the alternative method to undergo the experiment. So to make sure that all the objectives for the Projek Sarjana Muda is achieved, the experiment and procedure must be done properly and also by referring the scope of the project.